ANALISIS POLA KONSUMSI KELUARGA MISKIN DI KOTA MEDAN - Yuliana Yuliana (Ekonomi dan Keuangan, 2014)
The Research titled “The Analysis of Consumption Models of Poor Families in Medan”. The type of data used in this study is primary data with a sample of 100 people. Research methods used in this analysis is a qualitative descriptive method, using data tabulation frequency distribution and percentages.Tabulation of the results showed that the average income of poor families around Rp 600,000, - per month to the average food expenditure every month for Rp371.000, - and for non-food expenditure for Rp318.000, - every month. The average level of expenditure for most poor families food is rice that is equal to Rp180.000,- every month and the average level of expenditure for the largest non-food poor families are housing that is equal to Rp200.000,- every month. All respondents do not have a residual income or even a minus, because the income they receive is minimal.Keywords: Income, Consumption, Residual Income/Saving